P-041 YI Modifiable Risk Factors for Hospital Readmission Among Patients with Inflammatory Bowel Disease in a Nationwide Database. (February 2017) - Barnes, Edward; Kochar, Bharati; Crockett, Seth; Martin, Christopher; Kappelman, Michael; Long, Millie; Korzenik, Joshua
Abstract : Background: Prior studies have suggested that disease activity alone is not a reliable predictor for hospital readmission among patients with inflammatory bowel diseases (IBD). Single center experiences have suggested that depression and chronic pain are significant risk factors for readmission. Given the cost burden associated with readmission, we aimed to identify modifiable risk factors for hospital readmissions at 90 days using the Nationwide Readmission Database (NRD). Methods: We performed a retrospective cohort study using 2013 data from the NRD, a nationally representative database from the Healthcare Cost and Utilization Project. Involving data from 21 states, the NRD can be used to create national estimates of readmission rates for all payers and the uninsured. International Classification of Diseases, ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes were used to identify adult patients with discharge diagnoses of ulcerative colitis (UC) or Crohn's disease (CD). Among patients >18 years of age with IBD, depression, chronic pain, comorbidity (as measured by the Charlson Comorbidity score) and other attributes during index admission were measured. Multivariable logistic regression was used to estimate factors associated with hospital readmission, controlling for confounders. Data were analyzed using SAS survey procedures and weighted to reflect national estimates. Results: Among 129, 103 hospitalizations of patients with IBD (62% CD and 38% UC), 30, 019 (23%) were readmitted within 90 days of the index hospitalization. In multivariate analysis, younger age, male gender, and longer index hospitalizations were associated with greater risk of readmission. Those patients with Charlson Scores of >3 demonstrated increased odds of readmission (OR 1.30, 95% confidence interval [CI] 1.24–1.37) as compared to patients with a Charlson Score of <1. When compared to patients admitted to metropolitan teaching hospitals, patients admitted to metropolitan non-teaching hospitals (OR 0.90, 95% CI, 0.87–0.93) and non-metropolitan hospitals (OR 0.80, 95% CI, 0.76–0.85) demonstrated lower odds of readmission. Patients diagnosed with a small bowel obstruction (OR 1.05, 95% CI, 1.01–1.10) or a fistula (OR 1.56, 95% CI, 1.46–1.70) during the index admission demonstrated increased odds of readmission within 90 days. In addition, multiple modifiable risk factors for readmission were identified, including concurrent diagnoses of depression (OR 1.18, 95% CI, 1.13–1.23), chronic pain (OR 1.42, 1.35–1.49), and current tobacco use (OR 1.08, 95% CI, 1.04–1.13). Conclusions: Hospital readmission represents a significant burden for patients with IBD, with 23% of patients being readmitted within 90 days of initial discharge. Modifiable risk factors for readmission such as depression, chronic pain and tobacco use may represent targets for interventions to prevent hospital readmission with 90 days among IBD patients. Recognition of additional risk factors for readmission may also aid in efforts at decreasing readmission rates among patients with IBD.